2010
DOI: 10.1614/wt-d-09-00036.1
|View full text |Cite
|
Sign up to set email alerts
|

Weed-Competitive Ability of Spring and Winter Cereals in the Northern Great Plains

Abstract: The inclusion of winter cereals in spring-annual rotations in the northern Great Plains may reduce weed populations and herbicide requirements. A broad range of spring and winter cereals were compared for ability to suppress weeds and maximize grain yield at Lacombe (2002 to 2005) and Lethbridge (2003 to 2005), Alberta, Canada. High seeding rates (≥ 400 seeds/m2) were used in all years to maximize crop competitive ability. Spring cereals achieved high crop-plant densities (> 250 plants/m2) at most sites, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 21 publications
6
78
2
2
Order By: Relevance
“…The yield component for which triticale demonstrated a consistent superiority was KNO, which was largely generated by a higher level of KPE at similar levels of EPM. According to Beres et al (2010), triticales tiller less readily than bread wheat, whereas Giunta et al (2015) showed that tillering capacity in triticale is highly cultivar-dependent, and is generally superior to that of durum wheat. It is probable that the relatively high sowing density used was not permissive of a full expression of potential species differences in tillering capacity: most of the 450 ears m −2 were borne on the main stem (the mean number of tillers per plant was 0.3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield component for which triticale demonstrated a consistent superiority was KNO, which was largely generated by a higher level of KPE at similar levels of EPM. According to Beres et al (2010), triticales tiller less readily than bread wheat, whereas Giunta et al (2015) showed that tillering capacity in triticale is highly cultivar-dependent, and is generally superior to that of durum wheat. It is probable that the relatively high sowing density used was not permissive of a full expression of potential species differences in tillering capacity: most of the 450 ears m −2 were borne on the main stem (the mean number of tillers per plant was 0.3).…”
Section: Discussionmentioning
confidence: 99%
“…The former has been growing in popularity as a source of livestock feed, and is more recently being promoted as a feedstock for bioethanol production (Beres et al, 2010;Pejin et al, 2009). The characteristic feature of the Mediterranean environment is the high probability of terminal drought, while moisture stress during the winter months is rare (Loss and Siddique, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Triticale is uniquely different from other cereals in nutritional quality and broader adaptability. It also has a higher yield potential, is generally more competitive with weeds than wheat and displays better tolerance to drought and pests than its ancestral species [1, 3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Variation in the response to fall N fertilization may be due to differences in cold-tolerance among cultivars and in severity of cold temperature stress. The competitive ability of winter cereals with weeds can be substantially reduced by winterkill of the crop (Beres et al 2010b).…”
mentioning
confidence: 99%